Towards an integral fisheries management in the Apure River basin Venzuela - Pérez, Alfredo; Barbarino, Aniello; Castillo, Otto; Fabré, Nídia Noemí (Interciência, 2011)
The goal of this study was to make recommendations to the fishery resource management in western savannas of Venezuela. We propose a new approach for sustainable development of hydrobiology resources, using precautionary, adaptive, ecosystem and co-management ideas adjusted to current economic, social, and cultural traditions, and put them into action through pilot projects at different scales. In Venezuela, although fisheries have a considerable history, ecology, fishery and economic fisheries management tools have seldom been applied to tools of inland fisheries management. Any fisheries management plan for the Apure River drainage, must have a set of strategies and tactics O objetivo deste trabalho e recomendar acoes para a ordenacao dos recursos pesqueiros nas Planicies Ocidentais da Venezuela, procurando seu desenvolvimento sustentável, a traves de novos enfoques (precautorio, adaptativo, ecossistemico e manejo participativo), ajustando os interesses economicos sociais e culturais da sociedade, com o uso dos recursos hidrobiologicos mediante projetos pilotos pontuais em diferentes escalas. Na Venezuela, a pesar de ter uma consideravel trajetoria pesqueira, escassamente tem sido utilizadas ferramentas ecologicas, economicas ou pesqueiras, para o manejo das pesqueiras continentais. Portanto, um planejamento do manejo pesqueiro para a bacia do rio Apure, deve compreender um for implementation, to guarantee the protection, conservation, and propagation of the fisheries resources, for both migratory or non-migratory fishes. To that end we suggest a set of directives needed to implement a hybrid fisheries management system in the Apure Basin that incorporates the advantages of adaptive management and participatory co-management using synchronic management. In Venezuela the institutional and legal framework already exists to implement effective fisheries management, but political will to is lacking too bring fishermen, managers and research scientists together to make sustainable fisheries management a reality in the Apure Basin.
Hacia un manejo pesquero integral en la cu enca del Río Apure, Venezuela
Keywords: Pisces